Information Security Management Systems (ISMS) and Computer Security Self-Efficacy (CSSE) model comparison - Al-Shawabkeh, Mahmoud M. M.; Mohd Saudi, Madihah; Mohd Alwi, Najwa Hayati; Azman, Norhidayah (2016)
Information security models designed based on a different set of assumptions which are based on the characteristics of information system, motivations of organization to protect information, goals of the attacker and data validation of the model. The threats to information security are real and growing. Financial organizations need to take protective measures by implementing security policies though effective resource allocation is very difficult. This situation is due to uncertainty about the nature and severity of the threats and vulnerabilities and the effectiveness of the mitigation measures. Varieties of security policy models have been proposed to the financial organizations. Therefore to overcome the stated issues, this paper presents an analysis of two commonly used models: the Information Security Management System ISO/IEC 27001:2015 and Computer Security Self-Efficacy (CSSE). Findings confirm the suitability of both models for e-Banking computer security policies.